Birds of prey : and the fantabulous emancipation of one Harley Quinn [videorecording (Blu-Ray + DVD)] - Hodson, Christina; Robbie, Margot, 1990-; Perez, Rosie; Winstead, Mary Elizabeth; Smollett-Bell, Jurnee, 1986-; Novakovic, Bojana, 1981-; McGregor, Ewan, 1971-; Basco, Ella Jay, 2006-; Messina, Chris; Wong, Ali; Libatique, Matthew, 1969-; Pemberton, Daniel (Warner Bros. Home Entertainment, 2020)
A twisted tale told by Harley Quinn herself, as only Harley can tell it. When Gotham's most nefariously narcissistic villain, Roman Sionis, and his zealous right-hand, Zsasz, put a target on a young girl named Cass, the city is turned upside down looking for her. Harley, Huntress, Black Canary and Renee Montoya's paths collide, and the unlikely foursome has no choice but to team up to take Roman down.